WAYS TO INCREASE THE INCLUSIVE COMPETENCE OF PEDAGOGICAL STAFF OF SPECIAL NEEDS SUPPORT TEAM - Martynchuk, Olena; Skrypnyk, Tatiana; Naida, Julia; Sofiy, Natalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Inclusive education in Ukraine at the legislative level started more than 10 years ago, but analytical monitoring studies indicate that the level of education for children with SEN is unsatisfactory. The lack of an inclusive learning strategy andlow level of teachers` readiness to carry out the educational process for children with SEN together with their peers may be factors in this situation. The purpose of the study is to develop and implement an algorithm for enhancing the competence of teachers of inclusive classes.We conducted a training program in eight educational institutions (10 IEP teams), aimed at increasing the level of team interaction and inclusive competence of specialists.To assess the process of inclusive competence`s formation before and after the training program, we used Org-EIQ methodology, motivational orientation test, and teacher self-assessment method «Professional Development ToolforImprovingthe Quality of Practice in Primary School». As a result, all teachers have achieved a significant increase in the effectiveness of interdisciplinary support for children with special needs, which have reflected in the positive changes that have occurred in teachers at the professional, interpersonal and personal levels.